Ev vivo organ culture as potential prioritization tool for breast cancer targeted therapy. Issue 8 (3rd August 2018) - Grinshpun, Albert; Gavert, Nancy; Granit, Roy Zvi; Masuri, Hadas; Ben-Porath, Ittai; Breuer, Shani; Zick, Aviad; Rosenberg, Shai; Maoz, Myriam; Granit, Avital; Pikarsky, Eli; Strausmman, Ravid; et al.
ABSTRACT: The growing use of genomic testing presents new treatment options but also new dilemmas. We describe here a heavily-pretreated metastatic triple negative breast cancer patient who failed to respond to conventional treatment. Genomic analyses were performed that discovered several targetable alterations (e.g. FGFR1, CDK6, INSR) and created a clinical challenge – which target to target first? Our solution to this relatively common scenario was using ex-vivo organ culture (EVOC) system to prioritize treatment directed toward the best molecular target. EVOC enabled the trial of several potent targeted agents (Everolimus, Linsitinib, Palbociclib, AZD4547) and allowed semi-quantitative measurement of tumor response. The best response was to FGFR inhibitor, AZD4547. Consequently, the most accessible FGFR inhibiting agents (Pazopanib, then Nintedanib) were administered and some response was achieved. This report provides a potential rationale for utilizing EVOC system to predict tumor response to targeted therapy when multiple targets are proposed.